Co-Creation Tourism Storytelling on Weaving: Case Studies in Indonesia and Ghana - Ginting, Ina Veronika; Damanik, Janianton; Arymami, Dian; Teguh, Frans Xaverius (Technium Social Sciences Journal, 2025)
This study examines the role of co-creation storytelling practices in enhancing the cultural tourism experience within traditional weaving communities in Sikka, Indonesia, and Kumasi, Ghana. This research seeks to elucidate the processes through which narratives concerning traditional weaving are collaboratively constructed and disseminated among weavers, tour guides, local stakeholders, and tourists. This collaborative effort serves to enhance the authenticity and emotional resonance of the tourist experience. The study employed an ethnographic approach in Sikka through in-depth interviews, participatory observation, and document analysis, while literature review and secondary data were used to examine Kumasi. The findings indicate that storytelling functions not only as a means of cultural preservation but also as a strategic instrument in the development of cultural tourism. Through the process of co-creation, storytelling is revealed as a dialogic mechanism wherein diverse participants contribute to the development of meaningful and immersive experiences. Nonetheless, the study also underscores the tension between cultural authenticity and commodification within tourism contexts. Theoretically, this study advances the field of tourism literature by integrating the frameworks of cultural heritage, narrative theory, and co-creation. Practically, it underscores the significance of empowering local communities in the construction of narratives and engaging tourists as active participants.